Strategi Meningkatkan Daya Saing UMKM Kopi Dinodok Desa Bilalang Satu - Muhamad Zakir Mokoginta; Muharto Muharto; Aisya Mutiarasari (Lembaga Yasin AlSys, 2026)
The growth of local micro, small, and medium enterprises (MSMEs) needs to be continuously encouraged to enhance development and competitiveness; however, some MSMEs, such as Kopi Dinodok in Bilalang Satu Village, Kotamobagu City, still exhibit relatively slow progress. This study aimed to formulate strategies to improve the competitiveness of the Kopi Dinodok MSME, which produces pure robusta coffee with a distinctive flavor and has obtained certification from the Food and Drug Supervisory Agency (Balai POM) and an MD license. The research employed a descriptive qualitative approach with SWOT analysis, using data obtained through in-depth interviews with the owner, workers, and customers, field observations, and document analysis. The results of the analysis showed a total IFAS score of 2.97, with key strengths including product quality, official certification, government support, an organized production process, and customer loyalty, alongside weaknesses such as limited capital, low production capacity, and suboptimal digital marketing. The total EFAS score of 2.94 indicated major opportunities in the form of a growing coffee consumption trend, expanding local and national markets, government-provided training support, and potential collaboration with culinary business actors, while the enterprise also faces threats such as fluctuating coffee bean prices, intense competition, and limited production technology. The Cartesian SWOT Diagram analysis positioned the MSME in Quadrant I (aggressive strategy) with coordinates (1.85; 1.62), indicating that internal strengths can be optimally leveraged to capture external opportunities. It is concluded that strategies to enhance the competitiveness of Kopi Dinodok include market penetration, brand strengthening, product diversification, and the optimization of digital marketing, which in practical terms imply the development of innovative MSME business strategies based on local potential.